The Implementation of Audiolingual Methods on Ta'diyah Salam Material - Faizetul Ukhrawiyah; Dian Fajariyah Damayanti (Universitas Muhammadiyah Yogyakarta, 2021)
The objective of this research is to determine how the implementation of the Audiolingual method in Ta’diyah Salam material for the seventh grade students of MTS Darussalam Al-Qurani (Darussalam Al-Qurani Islamic Boarding School), Indramayu, what are the obstacles faced by teachers in implementing the method and how the efforts in overcoming these obstacles. The method the descriptive qualitative method with the data collection techniques used the observation, interviews, and documentation. From the results of the research, it is found that the audiolingual method used in the ta'diyah salam material uses the technique of dialog memorization, backward build up, and repetition drill. The obstacles faced by teachers in using the method are the limited time available for a well-implemented drilling system, the conditions of students who are not familiar with Arabic, as well as the fatigue and boredom experienced by students during the learning. However, as many obstacles appear, the teacher continues to strive to be able to overcome these obstacles by organizing the best possible time so that the learning can run well, conveying conversation texts as clearly as possible to the students, and providing learning media that are interesting for students so that they do not get bored quickly and tired.